Rough style architecture, interior, design - Kramer, Sibylle 1967- (Braun Publishing AG, 2015)
What was once considered incomplete and in need of repair, is chic and hip today: in new office buildings copper pipes are no longer hidden, but are exposed and artfully displayed against the raw formwork pattern of a concrete wall with ingenious lighting. Likewise, the unplastered, cracked walls of a restaurant in a former factory building are creatively altered with translucent modern textile materials. Rough Style presents buildings and spaces by architects and interior designers who work out expressive and most rigorous design concepts. Refraining from the accustomed ideals of beauty and perfection is the new approach. The uncompromising and exciting relationship in the encounter of innovative design schemes and raw unfinished states or traces of the past opens up new esthetic horizons, creating new standards of value.